Chronic villitis of unknown etiology and massive chronic intervillositis have similar immune cell composition. Issue 6 (June 2015) - Labarrere, C.A.; Hardin, J.W.; Haas, D.M.; Kassab, G.S.
Abstract: Introduction: Chronic villitis of unknown etiology (CVUE) and massive chronic intervillositis (MCI) are placental lesions associated with infiltration of mononuclear cells in the chorionic villi and the intervillous spaces, respectively. It is not well known whether immune cells in CVUE and MCI have similar phenotypic characteristics. Methods: A cross-sectional study of third trimester placentas was conducted to identify immune cell subpopulations in CVUE and MCI (n = 17/group). CVUE was diagnosed with H&E staining and antibody to CD3 in serial sections; and MCI, by the presence of massive infiltration of mononuclear cells in the intervillous spaces. Immune cells, ICAM-1 expression and nuclear factor κB (NF-κB) activation were determined immunohistochemically. Results: CVUE and MCI showed similar infiltrates, mainly CD68+ and CD3+ cells. Most cells (>80%) were CD45RB+, and one third were CD45RO+ in both lesions. There were slightly more CD8+ than CD4+ cells in both CVUE and MCI. More than 90% of cells in CVUE and MCI were ICAM-1+ with NFκB nuclear localization. Syncytiotrophoblast ICAM-1 expression was significantly (p < 0.001) higher in MCI (mean of 81.0; range of 71.6–86.0) than in CVUE (52.4; 36.4–59.4) or normal placentas (0.2; 0.0–0.6). Both, failure of physiologic transformation of spiral arteries and placental atherosclerosis-like lesions of atherosis were significantly more frequent in MCI than in CVUE or normal placentas (p = 0.044 and p = 0.007, respectively). Discussion: These finding suggest that MCI and CVUE have very similar infiltration of immune cells although MCI has more severe placental lesions. Highlights: Immunophenotypes of inflammatory/immune cells in MCI and CVUE are similar. Predominant infiltrates in both MCI and CVUE are CD68+ and CD3+ cells. Immune cells are activated (ICAM-1+ and NFκB+) in both MCI and CVUE. Failure of normal placentation and atherosis were more frequent in MCI than CVUE. MCI and CVUE seem to be similar lesions but MCI has more severe placental lesions.